The role of green accounting on profitability in listed mining companies - Indriani Suhardin; Winston Pontoh; Novi Budiarso (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the effect of environmental costs, environmental performance, and company size together on company profitability. The research used is quantitative research with a descriptive statistical approach. The data used is secondary data taken from financial reports and annual reports of mining companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This study uses multiple linear regression analysis. The results of this study indicate that environmental costs and company size have a negative and significant effect on profitability, while environmental performance has no effect on profitability.